(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The field of nutrigenomics, which investigates the intricate interplay between nutrition, genetics, and health outcomes, has witnessed significant advancements in recent years. These abstract aims to encapsulate the latest developments in nutrigenomics and personalized nutrition, highlighting key findings and methodologies shaping this rapidly evolving discipline.